CRIMINAL LAW AND HUMAN RIGHTS: A STUDY ON THE PRINCIPLE OF HUMAN RIGHTS PROTECTION IN ACEH QANUN NO. 6 OF 2014 ON JINAYAT LAW - Akbar, Khairil; Efendi, Sumardi (Universitas Islam Negeri Ar-Raniry, 2024)
This article aims to analyze the relationship between Islamic criminal law and human rights (HR), which are often seen as conflicting. Although criminal regulations, particularly the Qanun Jinayat, establish human rights protection as a principle, this does not imply that the Qanun Jinayat is entirely protective of or consistent with human rights. This study seeks to explain and assess whether Islamic criminal law contradicts human rights and to explore the relationship between Islamic criminal law and human rights. This article employs normative legal research methods. The materials used are obtained through library research and will be analyzed descriptively and prescriptively. The research results indicate that Islamic criminal law, particularly the Qanun Jinayat, is indeed difficult to reconcile with human rights, and in some aspects, it can be considered contradictory due to the nature of punishments, their methods of application, and the normative sources that recognize only one religion (Islam). For issues explicitly determined by religious texts (jarimah hudud), for instance, human rights principles are often disregarded, and Sharia provisions are fully applied. Nonetheless, the two cannot be separated. On one hand, human rights require law enforcement to properly address violations. Similarly, the Qanun Jinayat necessitates human rights principles to ensure that the punishments it prescribes uphold humanitarian principles, which are also the true objective of Sharia. The relationship between the two appears harmonious in matters categorized as jarimah/‘uqubat takzir, although improvements are still needed.